(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2016)
The purpose of this research is to determine the social, economic and financial impact generated by the use of the informal credit system and the banking credit system, in the merchants of the center of the city of Florence. This study was conducted through the descriptive and analytical approach, through the application of the structured instrument, survey, with a sample of 329 merchants, taken from a total population of 2,400 for 2015 according to the Chamber of Commerce. The results reveal that 153 people have formal credits, 182 informal credits, 41 currently use both systems and 35 have no credits.